Analysis of Antenatal Care Visit at the Work Area of Kilasah Health Centre Serang City in 2019 - Shinta Novelia; Rukmaini; Mulliawati Tohir (Nursing and Health Sciences Journal (NHSJ), 2021)
Background: Maternal mortality rate (MMR) in Indonesia was 359/100,000 live births, while in Banten Province it reaches 264 cases. The high rate of maternal and infant mortality is partly due to the frequency of irregular pregnancy check-ups. This is a problem because not all pregnant women check their pregnancy regularly so that abnormalities that arise in pregnancy cannot be detected as early as possible. Objective: This study aimed to analyze factors related to antenatal care (ANC) visits in the Kilasah Health Center Work Area Serang City in 2019. Methodology: The research method used was correlation research with a cross sectional study approach. The research sample was 91 midwives in the Work Area of ​​the Kilasah Health Center, Serang City. Results: From the results of the study, it was known that factors related to ANC visits in the Kilasah Health Center Work Area include knowledge (p = 0.023), education (p = 0.000), and family support (p = 0.004). Conclusions and Suggestions:. It is hoped that the the Health Centre more intensive in providing health education, so that public health knowledge will increase and there will be changes in public health behavior towards the better.